Biomarker expression and druggable gene alterations for development of an appropriate therapeutic protocol for pulmonary adenosquamous carcinoma. Issue 7 (5th February 2015) - Watanabe, Yukio; Shiraishi, Kouya; Takahashi, Fumiaki; Yoshida, Akihiko; Suzuki, Kenji; Asamura, Hisao; Takeuchi, Masahiro; Furuta, Koh; Tsuta, Koji
Abstract : Aims: Pulmonary adenosquamous carcinoma (ASC) is more aggressive than adenocarcinoma (AC) and squamous cell carcinoma (SCC). The genetic features and biomarkers of ASC are not well known. Here, we attempted to identify potential therapeutic markers for ASC. Methods and results: Surgically resected ASC samples from 65 patients were analysed. We examined the expression of β III‐tubulin, thymidylate synthase, breast cancer susceptibility gene 1 and ribonucleotide reductase M1 (RRM1); identified mutations in epidermal growth factor receptor ( EGFR ), KRAS, BRAF and HER2 ; and detected ALK, ROS1 and RET rearrangements. Gene amplification and expression of EGFR, human epidermal growth factor receptor 2 (HER2), fibroblast growth factor receptor‐1 and MET were also examined. β III‐Tubulin showed the highest expression ( P = 0.002), and its expression was more frequent in the AC than in the SCC component ( P = 0.013). RRM1 expression was more frequent in the SCC component ( P = 0.046). EGFR and KRAS mutations were detected in both components (21.5 and 10.9%, respectively). ALK and ROS1 rearrangements and MET amplification were detected in both components in one (1.5%) case. Conclusions: In ASC, drug response‐specific gene alterations could occur in both AC and SCC components, suggesting that patients with confirmed or suspected ASC should undergo further testing for driver gene analyses.